Efficacy and safety of lacosamide in the treatment of status epilepticus in a patient with comorbidities - Mascolo, Alfredo Paolo; Marrama, Federico; Mercuri, Nicola Biagio; Placidi, Fabio (Acta Biomedica Atenei Parmensis, 2021)
Efficacy, safety and tolerability of lacosamide in the treatment of status epilepticus are well described. However, other evidence of its pharmacologic profile in elderly patients with other comorbidities seems warranted. We describe the case of an 80 year-old woman with an history of arterial hypertension, ischemic cardiomyopathy, COPD, CKD, previous laryngeal cancer, a stoma positioning for diverticular disease and previous surgery for a left frontal meningioma. Since then, the patient developed focal epilepsy and she was on levetiracetam and valproic acid therapy. The patient was admitted to our department for a focal status epilepticus characterized by non-fluent aphasia and right facio-brachial clonic movements. She also presented with aspiration pneumonia and started intravenous antibiotic treatment. After failure of a first-line antiepileptic drug, lacosamide intravenous treatment was started, with complete reversal of the clinical picture. EEG then showed focal slow waves mixed to interictal epileptiform discharges over the left fronto-temporal regions. The patient was then discharged home with an oral lacosamide treatment and at 3 months she was seizure-free. Our case report confirms the efficacy of lacosamide in status epilepticus, highlighting its safety and tolerability in an elderly and fragile patient with multiple comorbidities and drug therapy.